2021
DOI: 10.3390/antiox10121983
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of 3′,4′-Dihidroxifenilglicol and Hydroxytyrosol on Oxidative and Nitrosative Stress and Some Cardiovascular Biomarkers in an Experimental Model of Type 1 Diabetes Mellitus

Abstract: The objective of this study was to assess a possible synergistic effect of two extra-virgin olive oil polyphenols, 3,4,-dyhydroxyphenylglycol (DHPG) and hydroxytyrosol (HT), in an experimental model of type 1 diabetes. Seven groups of animals were studied: (1) Nondiabetic rats (NDR), (2) 2-month-old diabetic rats (DR), (3) DR treated with 5 mg/kg/day p.o. HT, (4) DR treated with 0.5 mg/kg/day p.o. DHPG, (5) DR treated with 1 mg/kg/day p.o. DHPG, (6) DR treated with HT + DHPG (0.5), (7) DR treated with HT + DHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…The synergism between phenolic compounds could explain the superiority of whole OOs or phenolic extracts against pure phenolic compounds to inhibit platelet activation. A recent study of De La Cruz Cortés et al [57], clearly showed the synergistic effect of HT and DHPG in similar proportions found in EVOO to attenuate COL-induced platelet aggregation of diabetic rats and to spare prostacyclin synthesis by the aorta.…”
Section: Effect Of Phenolic Compounds/extracts Of Oo On Platelet Func...mentioning
confidence: 69%
See 2 more Smart Citations
“…The synergism between phenolic compounds could explain the superiority of whole OOs or phenolic extracts against pure phenolic compounds to inhibit platelet activation. A recent study of De La Cruz Cortés et al [57], clearly showed the synergistic effect of HT and DHPG in similar proportions found in EVOO to attenuate COL-induced platelet aggregation of diabetic rats and to spare prostacyclin synthesis by the aorta.…”
Section: Effect Of Phenolic Compounds/extracts Of Oo On Platelet Func...mentioning
confidence: 69%
“…The majority of the studies used rats as the preferred animal species while only one study used New Zealand rabbits. The pathological phenotypes induced by the researchers were either atherosclerosis (induced by an atherogenic diet) [55], diabetes (induced by streptozotocin) [56,57] while the rest of the intervention studies were conducted in healthy animals. The investigators administered [57] Rats (male Wistar) NDR: saline-treated non-diabetic rats either VOO [55,56,58], EVOOs with different concentrations of phenolics [59], HT [57,60], HTA [60], DHPG [57] and alkyl ether derivatives of HT [61].…”
Section: Effect Of Phenolic Compounds/extracts Of Oo On Platelet Func...mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet in vitro studies or animal models, even not concerning skeletal muscle, showed an interest in using a mixture of polyphenols. In fact, such a mixture of polyphenols is more active than each individual molecule alone as a synergy effect occurs between the molecules [ 205 , 206 ].…”
Section: Discussionmentioning
confidence: 99%
“… HT treatment decreased HDAC11 and HDAC11 mRNA expression. [ 34 ] Wistar rats (n = 60) Non-Diabetic rats Diabetic rats Diabetic + 5 mg/kg/day HT rats Diabetic + 0.5 mg/kg/day DHPG rats Diabetic + 0.5 mg/kg/day DHPG + HT rats Diabetic + 1 mg/kg/day DHPG + HT rats Every treatment were administrated in the drinking water once a day during 7 days before diabetes’ induction. Then, every treatment were administrated daily during 2 months.…”
Section: Hydroxytyrosol In Animal Studiesmentioning
confidence: 99%